Simulações computacionais da corrente de inrush no transformador de potência - PINHEIRO, André Veiga (2018)
This work studies a transient effect on the transformer inrush current, that arise in the moment of energizing and reenergizing. Is shown of literary form the emergence and the effects of current in power transformers and its methods for its reduction. A computational study was conducted through the ATP software, simulating a real 15 MVA transformer, the inrush current simulations was made so the development of didactic work seeking a greater understanding of the phenomena involved, we used the actual parameters of the power transformer used in substation of the Tucuruí hydropower complex. Made the inrush current simulation was analyzed the results obtained and compared with the actual results of the book testing performed by the manufacturer, is obtained the representation of second harmonic in the first relation, and is used the method to insert a pre-insertion resistor to reduce inrush current.